Asthma Is Associated with Multiple Alterations in Anti-Viral Innate Signalling Pathways - Pritchard, Antonia L.; White, Olivia J.; Burel, Julie G.; Carroll, Melanie L.; Phipps, Simon; Upham, John W. (PloS one, 2014)
Human rhinovirus (HRV) infection is a major trigger for asthma exacerbations. Anti-viral immunity appears to be abnormal in asthma, with immune dysfunction reported in both airway structural cells and migratory, bone marrow derived cells. Though decreased capacity to produce anti-viral interferons (IFNs) has been reported in asthma, a detailed analysis of the molecular events involved has not been undertaken. To compare the molecular pathway controlling type I IFN synthesis in HRV-stimulated peripheral blood mononuclear cells (PBMC) from asthmatic and healthy subjects. PBMC from 22 allergic asthmatics and 20 healthy donors were cultured with HRV for 24 hours. Multiple components of the Toll-like receptor (TLR), IFN regulatory and NFκβ pathways were compared at the mRNA and protein level. Multiple deficiencies in the innate immune response to HRV were identified in asthma, with significantly lower expression of IFNα, IFNβ and interferon stimulated genes than in healthy subjects. This was accompanied by reduced expression of intra-cellular signalling molecules including interferon regulatory factors (IRF1, IRF7), NF-κB family members (p50, p52, p65 and IκKα) and STAT1, and by reduced responsiveness to TLR7/TLR8 activation. These observations could not be attributed to alterations in the numbers of dendritic cell (DC) subsets in asthma or baseline expression of the viral RNA sensing receptors TLR7/TLR8. In healthy subjects, blocking the activity of type-I IFN or depleting plasmacytoid DC recapitulated many of the abnormalities observed in asthma. Multiple abnormalities in innate anti-viral signalling pathways were identified in asthma, with deficiencies in both IFN-dependent and IFN-independent molecules identified.